Technologies of Concealment: Appropriateness, Effectiveness, and Motivations for Hiding Organizational Identity. Issue 2 (15th March 2018) - Dwyer, Maria; Sahay, Surabhi; Scott, Craig R.; Dadlani, Punit; McKinley, Erin
Abstract : Some organizations and their members use, or limit the use of, technologies to conceal their identity. This study explores, from a receiver perspective, the perceived appropriateness and effectiveness of concealment technologies and how different motivations to conceal affect those assessments. A survey of 120 adults reveals that various technologies are similarly effective at concealing organizations, but differ in terms of appropriateness. Protecting one's identity consistently relates to judgments regarding acceptability of using concealment technologies. This research adds to theories about communication technologies and extends work related to the receiver model and motivations for anonymity.